The value of novel invasive hemodynamic parameters added to the TIMI risk score for short-term prognosis assessment in patients with ST segment elevation myocardial infarction. (1st July 2016) - Tesak, Martin; Kala, Petr; Jarkovsky, Jiri; Poloczek, Martin; Bocek, Otakar; Jerabek, Petr; Kubková, Lenka; Manousek, Jan; Spinar, Jindrich; Mebazaa, Alexandre; Parenica, Jiri; Cohen-Solal, Alain
Abstract: Background: We compared the prognostic capacity of conventional and novel invasive parameters derived from the slope of the preload recruitable stroke work relationship (PRSW) in STEMI patients and assessed their contribution to the TIMI risk score. Methods: Left ventricular end-diastolic pressure (EDP), ejection fraction (EF), pressure adjusted maximum rate of pressure change in the left ventricle (dP/dt/P), aortic systolic pressure to EDP ratio (SBP/EDP) and end-diastolic volume adjusted stroke work (EW), derived from the slope of the PRSW relationship, were obtained during the emergency cardiac catheterization in 523 STEMI patients. The predictive power of the analyzed parameters for 30-day and 1-year mortality was evaluated using C-statistics and reclassification analysis was adopted to assess the improvement in TIMI score. Results: The highest area under the curve (AUC) values for 30-day mortality were observed for EW (0.872(95% confidence interval 0.801–0.943)), SBP/EDP (0.843(0.758–0.928)) and EF (0.833(0.735–0.931)); p < 0.001 for all values. For 1-year mortality the best predictive value was found for EW (0.806(0.724–0.887) and EF (0.793(0.703–0.883)); p < 0.001 for both. The addition of EDP, SBP/EDP ratio and EW to TIMI score significantly increased the AUC according to De Long's test. For 30-day mortality, increased discriminative power following addition to the TIMI score was observed for EW and SBP/EDP (Integrated Discrimination Improvement was 0.086(0.033–0.140), p = 0.002 and 0.078(0.028–0.128), p = 0.002, respectively). Conclusions: EW and SBP/EDP are prognostic markers with high predictive value for 30-day and 1-year mortality. Both parameters, easily obtained during emergency catheterization, improve the discriminatory capacity of the TIMI score for 30-day mortality.